2021
DOI: 10.1111/cas.14994
|View full text |Cite
|
Sign up to set email alerts
|

Connexin32 activates necroptosis through Src‐mediated inhibition of caspase 8 in hepatocellular carcinoma

Abstract: Necroptosis is an alternative form of programmed cell death that generally occurs under apoptosis‐deficient conditions. Our previous work showed that connexin32 (Cx32) promotes the malignant progress of hepatocellular carcinoma (HCC) by enhancing the ability of resisting apoptosis in vivo and in vitro. Whether triggering necroptosis is a promising strategy to eliminate the apoptosis‐resistant HCC cells with high Cx32 expression remains unknown. In this study, we found that Cx32 expression was positively correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 39 publications
(82 reference statements)
0
10
0
Order By: Relevance
“…Necroptosis affects tumorigenesis, infiltration, and metastasis, thereby affecting cancer prognosis. Accumulating evidence suggested that necroptosis not only mediates physiological regulation but also results in inflammatory pathologies and various cancers such as gastric cancer, colorectal cancer, cholangiocarcinoma, pancreatic cancer, and hepatocellular carcinoma [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Necroptosis affects tumorigenesis, infiltration, and metastasis, thereby affecting cancer prognosis. Accumulating evidence suggested that necroptosis not only mediates physiological regulation but also results in inflammatory pathologies and various cancers such as gastric cancer, colorectal cancer, cholangiocarcinoma, pancreatic cancer, and hepatocellular carcinoma [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Inhibited caspase 8 was considered to indicate necroptosis induction [ 71 ]. In parental and sunitinib-resistant Caki-1 and 786-O cells, treatment with SHI caused a significant reduction in caspase 8 activity, whereas the activity of caspases 3/7 and 9 remained unchanged, further indicating necroptosis initiation in these RCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Under inactivated caspase 8 conditions, RIP1 and RIP3 phosphorylate each other and form the necrosome complex. Xiang et al [ 71 ] have described the activation of necroptosis in liver carcinoma cells via inactivated caspase 8 and preserved RIP1 and RIP3 from caspase 8-dependent cleavage, thereby inducing necroptosis. In suitable agreement with the present findings, SHI has been shown to abrogate the activation of caspases 3 and 8 in multiple myeloma [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…And, necroptosis, as a form of programmed cell death, was considered as a promising approach to eliminate cancer cells [25]. The potential molecular mechanisms of NRGs and their prognostic value in LIHC were rarely discussed [26]. Elucidating the prognostic 10 Disease Markers performance and potential regulatory axis of NRGs in LIHC will help clinicians to explore the effect of necrotosis on the prognosis and treatment of LIHC.…”
Section: Discussionmentioning
confidence: 99%